Die Stadt als beschriebener Raum Die Beispiele Pompeji und Herculaneum - Opdenhoff, Fanny (Materiale Textkulturen, 2021)
Today's visitors to Pompeii and Herculaneum encounter a vast profusion of written evidence. Painted announcements stand alongside inscribed notices and monumental stone inscriptions. The content is as varied as the conditions of creation and situations that once confronted the ancient reader. This demonstrates in singular fashion the interconnections between the context, action, content, and materiality of the texts.